Selenium supplementation for the preterm Indian neonate - Geeta Gathwala; Rahul Aggarwal (Wolters Kluwer Medknow Publications, 2016)
Deficient antioxidant defenses in preterm infants have been implicated in diseases such as bronchopulmonary dysplasia, retinopathy of prematurity, necrotizing enterocolitis, periventricular leukomalacia, and intraventricular hemorrhage. The antioxidant properties of selenium make it important in the nutrition of very low-birth weight (VLBW) infants. Selenium is a component of glutathione peroxidase (GPX), an enzyme that prevents the production of free radicals. Preterm infants have low selenium stores and require supplementation by parenteral and enteral routes. This communiquι reviews the beneficial role that selenium supplementation might play in improving neonatal outcomes.